DESKRIPTIF KUANTITATIF DUKUNGAN SOSIAL PADA KEPALA SEKOLAH KELOMPOK BERMAIN (KB) DAN TAMAN KANAK-KANAK (TK) AISYIAH KABUPATEN GRESIK - Amelasasih, Prianggi (Psikosains: Jurnal Penelitian dan Pemikiran Psikologi, 2024)
Background: The many duties, roles and responsibilities of the school principalare in direct contact with teachers, school staff and the community around theschool environment, so there is a need for social support from the partiesconcerned. The existence of this social support can make it easier for schoolprincipals to carry out all activities related to school services. Objective: Thisresearch aims to look at social support for school principals so that they canimprove and maintain physical health and psychological well-being. Thisresearch measures a single variable, namely social support. Method: Theresearch subjects were 71 principals of KB and Aisyiah Kindergarten schools inGresik Regency. Data collection used a questionnaire with a Likert scale tomeasure the level of social support, consisting of 10 items. The data analysistechnique used is descriptive statistics via the SPSS for Windows application.Result: Based on the results of the t test analysis, the difference in t value is37,369 and the significance value between the mean value of the KB and TKlevels in getting social support is p value 0.000 < 0.05. This shows that there isa significant difference between social support for KB and TK. With an empiricalmean value for the KB level of 37.47 and an average empirical mean for the TKof 39.28. Conclusion: Level TK level has a greater empirical mean value thanKB level, which shows that the TK school level has higher social support thanKB school level